Mutagen sensitivity and p53 expression in colorectal cancer in China. Issue 913 (1st November 2001) - Shao, L; Lai, M; Huang, Q
Abstract : OBJECTIVE: This study was designed to investigate DNA damage and/or repair capability, non-random chromatid breakage, and p53 expression in patients with colorectal cancer. METHODS: The bleomycin sensitivity assay was used in a case-control study to compare the DNA damage repair system between colorectal cancer patients and controls. G-banding was used to search for non-random chromatid breaks. Immunocytochemistry was used to investigate p53 expression in tumour tissues and adjacent normal tissues. RESULTS: It was found that cases typically had a higher number of chromosome breaks than controls (0.84 v 0.69 breaks/cell, p<0.01). After correction by sex and age, the difference was still significant (F=4.38, p<0.05). The correlation coefficient between mutagen sensitivity and age was 0.31(p<0.05) in controls and 0.18 (p>0.05) in cases. The ratio of odds ratios among bleomycin resistant, sensitive, and hypersensitive classes was 1:2.31:3.85. Overexpression of p53 was detected in 25 of 47 tumour tissues independent of tumour stage. Cases who had a family history of cancer were susceptible to the p53 aberration (p<0.05). Chromosomes 1p, 5q, and 14q were susceptible to breakage in patients with colorectal cancer. CONCLUSION: Patients with colorectal cancer show increased bleomycin induced chromatid breaks and may have minor DNA repair deficiencies. p53 aberration is an early event in the development of colorectal cancer, but no definite correlation is found between p53 overexpression and mutagen sensitivity.